Pelatihan Pembuatan Artikel Ilmiah Dari Hasil Skripsi Dan Cara Mempublish di Jurnal Pada Mahasiswa STIE LMII - Nera Mayana Br Tarigan Nera Mayana Br Tarigan; Ricky Martin Ginting Ricky Martin Ginting; Santa Elisa Br Tarigan Santa Elisa Br Tarigan (Cv. Utility Project Solution, 2022)
The results of student research (thesis) have been achieved both in the form of university repositories and in scientific journals. In accordance with the circular letter of the Directorate General of Learning and Student Affairs Number: B/565/B.B1/HK.01.01/2019 on July 8, 2019, concerning Facilities for Publication of Student Scientific Work. STIE LMII is a higher education institution that produces graduates by conducting research as a requirement to graduate as a management graduate. However, with the circular mentioned above, STIE LMII students are still confused about publishing scientific papers from the results of their thesis. Both in terms of making scientific articles from the results of their thesis and how they are published in scientific journals. So from this problem the community service team aims to conduct training in making scientific articles from the results of student research/thesis and training on how to publish scientific articles in scientific journals. That STIE LMII students are very interested and participate in the training easily following the material. STIE LMII students who take part in the training make scientific articles from the results of the research/thesis.